Cardiovascular adverse events by non-steroidal anti-inflammatory drugs: when the benefits outweigh the risks. Issue 11 (1st November 2016) - Zingler, Gerhard; Hermann, Birgit; Fischer, Tim; Herdegen, Thomas
ABSTRACT: Introduction : Therapeutic efficiency of NSAID is handicapped by ongoing discussion of cardiovascular (CV) safety. Areas covered : We update meta-analyses on NSAIDs in patients with and without cardiovascular (CV) diseases and analyse the association between NSAIDs and cardiovascular events in patients with inflammation. We demonstrate the substantial influence of an indication bias and confounding, which falsely increase the CV risk. We demonstrate protective cardiovascular effects of NSAIDs due to their anti-inflammatory activity, in particular in patients with rheumatoid arthritis, osteoarthritis or inflammatory pain. Expert commentary : t-NSAIDs and Coxibes drugs resemble in their observed CV risk which, in contrast, reflects the intrinsic risk of patients with pain and inflammation. The anti-inflammatory NSAIDs reduce the risk of first myocardial infarction in patients with inflammation and elevated CRP. The extended use of NSAIDs is not associated with an increased CV risk in patients with pain and inflammation but with reduction in all-cause mortality.